2023
DOI: 10.3390/urbansci7030071
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Quality of Some Parts of Coastal Bhola District, Bangladesh: Exceptional Evidence

Abstract: The composition of groundwater governs the drinking and irrigation water suitability. A large part of the coastal region of Bangladesh is affected and is responsible for changing the composition of the groundwater. This research attempted to observe the groundwater quality of the Bhola Sadar and Char Fasson upazilas in coastal Bangladesh. Twenty-eight (28) water samples, 27 at depths of 260–430 m (850–1400 ft) and 1 from a crop field, were collected and analyzed. The quality of water samples was determined thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…These findings have been in compliance to a recent study conducted in a neighboring area by [12] where the average pH reading was reported as 7.12. Moreover, investigations carried out in coastal regions of China [45] and Bangladesh [46] have reported a similar average pH range of 7-8.…”
Section: Physical Parametersmentioning
confidence: 77%
See 1 more Smart Citation
“…These findings have been in compliance to a recent study conducted in a neighboring area by [12] where the average pH reading was reported as 7.12. Moreover, investigations carried out in coastal regions of China [45] and Bangladesh [46] have reported a similar average pH range of 7-8.…”
Section: Physical Parametersmentioning
confidence: 77%
“…In terms of electrical conductivity (EC), readings varied from 2062.97 µS/cm to 14114.58 µS/cm, averaging 6715.78 µS/cm, exceeding the permissible limit. A recent study on coastal groundwater in Bhola District, Bangladesh, reported an average EC of 588.15 µS/cm [46], indicating a notable difference between the two reports. However, the EC values observed in this study align with those found in coastal aquifers of Southern Kenya [47], Western Cape Province, South Africa [48], and South [49].…”
Section: Physical Parametersmentioning
confidence: 88%
“…Turning to the practical standpoint of this research work, it is worth mentioning that the sustainable management of water resources in often challenging due to financial compliance, institutional framework, requirement of sophisticated analytical procedure and establishment, lack of skilled human resources [ [ 31 , [114] , [115] , [116] , [117] , [118] , [119] ]]. Developed countries in the world mitigate these challenges through regional management tools (e.g., Water Framework Directive for European countries) but it remains as a tremendous challenge for developing countries like Bangladesh.…”
Section: Resultsmentioning
confidence: 99%
“…In some districts, water is suitable for irrigation purposes, whereas in some districts, there is a shortage of safe drinking water during the dry season. Heavy metals or metalloids and salinity intrusion are also sometimes found in groundwater [ [36] , [37] , [38] ]. To ensure safe drinking water, knowledge of water pollution is important, as water, sanitation, and hygiene are the cause of 8.5 % of deaths in Bangladesh [ 39 ].…”
Section: Introductionmentioning
confidence: 99%